Analisis Strategi Pengembangan Usaha Batiah Anis Baduih di Nagari Simawang Kecamatan Rambatan Kabupaten Tanah Datar - Fauziah Elna Novita Sari; Himyar Pasrizal (Jurnal Manajemen Bisnis Syariah, 2024)
The aim of this research is to determine the internal and external factors in developing the Anis Baduih batiah business in Nagari Simawang, Rangkat District, Tanah Datar Regency and to explain the strategy for developing the Anis Baduih batiah business in Nagari Simawang, Rangkat District, Tanah Datar Regency. The research method uses a qualitative approach. Data collection techniques through observation, interviews and documentation. The research results show that Batiah Anis Baduih Business has tried to carry out development activities. The results of this research show that Anis Baduih's batiah business has internal factors in developing the business, especially the experience and expertise possessed by Mrs. Anis. Meanwhile, external factors in Anis Baduih's batiah business have not been maximized because the promotion process is only through word of mouth and has not used social media properly, so the market share is relatively small. The lack of collaborative partners in Anis Baduih's batiah business has had an impact on the business. It would be better if Anis Baduih's batiah business development strategy uses communication channels in the form of social media to promote Anis Baduih's batiah business, as well as establishing key partnerships to the maximum